THE COMPOSITION OF PURSE SEINE DURING THE DAY AND AT NIGHT IN THE SASAK JORONG PASA LAMO RANAH PASISIE, DISTRICT WEST PASAMAN, WEST SUMATERA PROVINCE - Agus Muliadi; Pareng Rengi; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRAKThis research was conducted on March 17th to July 21th 2014, in the Sasak Jorong Pasa Lamo Ranah Pasisie, District West Pasaman, West Sumatera Province. The purpose of this study was to determine the differences in the composition of purse seine during the day and at night.This research used a survey method. The operation of purse seine fishing gear held on over 5 days of arrest.The Purse seine catches consist of 10 species, either in the day or at night with the weight was 620 kg at noon (1,625 fishes) and at night was 4.813kg (6,390 fishes), overall the weight were 5433 kg (8,015 fishes). The species of fish which were caught consist of Acanthocybium solandri, Auxis thazard, Stromsteus niger, Selaroides leptolepis, Caranax melampygus, Leioghnathus equulus, Rastrelliger faughni, Scilla serrate,Chrysaora quinquecirrha, Lolygo sp.T-test and Chi-square test showed that there is no differences in the average and composition of catches during the day and at night.Keyword: Purse seine, the day, at night, West sumatera.